The intensity, duration, and severity of low aragonite saturation state events on the California continental shelf. Issue 13 (3rd July 2013) - Hauri, C.; Gruber, N.; McDonnell, A. M. P.; Vogt, M.
<x xml:space="preserve">Abstract</x> [1] Ocean acidification will progress in an episodic manner, yet this has rarely been considered. Here, we investigate how the intensity, duration, and severity of episodic low aragonite saturation state events along the California continental shelf have changed since 1750, and how they might change up to 2050 under the A2 scenario from the Special Report on Emissions Scenarios by the Intergovernmental Panel on Climate Change. Our model‐based results suggest that between 1750 and 2010, aragonite undersaturation events along the shelf have quadrupled in their number and lengthened in duration, but that even larger changes are bound to occur within the next 20 to 40 years. Undersaturation will become very likely the norm near the seafloor by 2030, and if atmospheric CO2 increases beyond 500 ppm, this layer will become permanently undersaturated. Combined with a fourfold increase in intensity, the resulting increase in severity of low aragonite saturation state events will substantially affect the viability of calcifying organisms and will alter ecosystem structure.